Alterations in amplitude of low frequency fluctuation in treatment‐naïve major depressive disorder measured with resting‐state fMRI. Issue 10 (17th April 2014) - Liu, Jie; Ren, Ling; Womer, Fay Y.; Wang, Jue; Fan, Guoguang; Jiang, Wenyan; Blumberg, Hilary P.; Tang, Yanqing; Xu, Ke; Wang, Fei
Abstract There are limited resting‐state functional magnetic resonance imaging (fMRI) studies in major depressive disorder (MDD). Of these studies, functional connectivity analyses are mostly used. However, a new method based on the magnitude of low frequency fluctuation (LFF) during resting‐state fMRI may provide important insight into MDD. In this study, we examined the amplitude of LFF (ALFF) within the whole brain during resting‐state fMRI in 30 treatment‐naïve MDD subjects and 30 healthy control (HC) subjects. When compared with HC, MDD subjects showed increased ALFF in the frontal cortex (including the bilateral ventral/dorsal anterior cingulate cortex, orbitofrontal cortex, premotor cortex, ventral prefrontal cortex, left dorsal lateral frontal cortex, left superior frontal cortex), basal ganglia (including the right putamen and left caudate nucleus), left insular cortex, right anterior entorhinal cortex and left inferior parietal cortex, together with decreased ALFF in the bilateral occipital cortex, cerebellum hemisphere, and right superior temporal cortex. These findings may relate to characteristics of MDD, such as excessive self‐referential processing and deficits in cognitive control of emotional processing, which may contribute to the persistent and recurrent nature of the disorder. Hum Brain Mapp 35:4979–4988, 2014. © 2014 Wiley Periodicals, Inc.